Validitas dan Reabilitas Soal Tes Uji Kemampuan Matematika Siswa Kelas V MIT Al Fuad Kota Tangerang - Magdalena, Ina; Ramadanti, Fitri; Tsania, Sholikhatu; Fauzi, Hadana Nur; Rosita, Nurul; Arif, Syamsul (Lembaga Yasin AlSys, 2023)
This study aims to determine the validity and reliability of the mathematical ability tests used in measuring the effectiveness of learning mathematics using modules. The tests compiled were validated by experts including mathematics education lecturers and mathematics teachers and the results are valid and can be used without revision. In this study using a quantitative approach and using the interview method, this method focuses on the problem directly as it was at the time the research took place. Then the test was tested o n fifth grade students at MIT AL-FUAD Tangerang City. There are as many as 4 tests of mathematical ability tested. The ability test test 1 contains materials for linear equations and inequalities for one variable consisting of 5 questions. Ability test test 2 contains material on the equation of the absolute value of the linear variable one consisting of 3 questions. Ability test test 3 contains material on the linear absolute value inequality of one variable consisting of 3 items. The ability test test 4 contains material on a three-variable system of linear equations consisting of 2 questions.